Proceedings from the Ice Hockey summit on concussion: A call to action - Smith, A. M.; Stuart, M. J.; Greenwald, R. M.; Benson, B. W.; Dodick, D. W.; Emery, C. A.; Finnoff, J. T.; Mihalik, J. P.; Roberts, W. O.; Sullivan, C. A.; Meeuwisse, W. H. (Clinical Journal of Sport Medicine, 2011)
Objective: The objective of this proceeding is to integrate the concussion in sport literature and sport science research on safety in ice hockey to develop an action plan to reduce the risk, incidence, severity, and consequences of concussion in ice hockey.